Pengaruh Leverage, Struktur Modal dan Konservatisme Akutansi terhadap Kinerja Keuangan Perusahaan - Nainggolan, Carlos Daniel (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2023)
This study discusses the performance of financial companies based on the results of previous literature. A number of articles and studies published in recent years have examined the factors that influence the performance of financial companies, such as leverage, capital structure and accounting conservatism. Research also evaluates the use of different metrics in measuring the performance of financial companies, such as financial ratios, trend analysis, and benchmarking. The results of this research show that the performance of financial companies is influenced by various internal and external factors, as well as the measurement methods used. This study aims to provide a better understanding of the performance of financial companies and the factors that influence it, so that it can help decision making in the future. Leverage, Capital Structure and Accounting Conservatism affect the company's financial performance. Keyword: Company Financial Performance, Leverage, Capital Structure and Accounting Conservatism